Factor content functions and the theory of international trade - Neary, J; Schweinberger, A (Review of Economic Studies Ltd, 1986)
This paper introduces the concepts of direct and indirect factor trade utility functions and uses them to derive Marshallian and Hicksian factor content functions, which express the quantities of factors of production embodied in net imports as functions of the exogenous variables facing the economy. The properties of these functions are discussed and they are used to derive a number of new results. In particular, it is shown that, in certain circumstances, the existence of gains from trade is sufficient for the Heckscher-Ohlin theorem to hold in its factor content form.